PRINCIPLES OF CREATIVE DEVELOPING EDUCATION FOR PRIMARY STUDENTS ON THE BASIS OF THE SEMIOTIC SYSTEM - Abdusamatov Alisher Sobirovich (Bright Mind Publishing, 2025)
This article provides information to junior students of general secondary schools on the semiotic approach, the areas of semiotics and their boundaries and types, the importance, history and application of semiotic aspects, necessary pedagogical conditions, scientists and their views, branches, directions and applications of semiotics. in our everyday life. It is described how we use it.
Keywords: Semiotics, education, educational system, philosophy, pragmatics, syntax.